1981
DOI: 10.1203/00006450-198115080-00009
|View full text |Cite
|
Sign up to set email alerts
|

Assessments of the Sensitivities of Cultured Human Neuroblastoma Cells to Anti-Tumour Drugs

Abstract: SummaryWhen logarithmically growing neuroblastoma cells were exposed in vitro for 24 hr to a range of concentrations of various antitumour drugs and then cloned in agar to assess colony-forming ability, the dose-response curves obtained were of two types only, namely exponential-plateau or exponential. The former category, included hydroxyurea, 1.1'-propylene bispiperazine-3.5-dione (ICRF-159). vincristine and vindesine. where the plateau was reached before 1 log cell kill, and 4'-demethylepipodophllotoxin the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This drug has previously been found to yield biphasic curves, and the initial slope has been suggested to represent the elimination of a sensitive (possibly S) subpopulation (Madoc-Jones and. Mauro,1968;Drewinko and Barlogie,1981;Hill and Whelan, 1981). The 16C+ curve in CHO-Kl approximated to an exponential whose slope was similar to the second clonogenic phase.…”
Section: Resultsmentioning
confidence: 99%
“…This drug has previously been found to yield biphasic curves, and the initial slope has been suggested to represent the elimination of a sensitive (possibly S) subpopulation (Madoc-Jones and. Mauro,1968;Drewinko and Barlogie,1981;Hill and Whelan, 1981). The 16C+ curve in CHO-Kl approximated to an exponential whose slope was similar to the second clonogenic phase.…”
Section: Resultsmentioning
confidence: 99%
“…The log‐linear in vitro dose‐response of cultured neuroblastoma cells to melphalan and other alkylating agents 10 provides a rationale for “high dose consolidation” chemotherapy (“megatherapy”) to try to overcome drug resistance 11. Since its introduction into clinical practice in 1977, high dose melphalan has been used by many centres to treat patients with advanced neuroblastoma, often in combination with either total body irradiation (TBI) or other high dose cytotoxic drugs 12–14.…”
Section: Introductionmentioning
confidence: 99%
“…It can now be seen, for example, after using the three lines that in our original study [1] the CHP100 cells were hypersensitive to amsacrine, methotrexate and vincristine, yet refractory to cisplatin and VP-16. So if we applied the effectiveness criteria, described earlier [1], on the basis of the three cell lines we would now exclude amsacrine as the most effective agent, but promote VP-16 and 'high-dose' cisplatin to join adriamycin and VM 26 and downgrade the Vinca alkaloids. Such a classification appears to fit more closely with clinical experience, since it has now been shown that amsacrine is ineffective against neuroblastoma [12], whilst VP-16 plus high-dose cisplatin has demonstrated activity in this disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…The same method described in detail earlier [1] was used for these neuroblastoma cell lines. Briefly, cells were plated at a density of 2 • 104/ml into 2 cm dishes and two days later, a range of concentration of each drug were added in 50/zl volumes to each dish.…”
Section: Soft Agarose Colony Forming Assaysmentioning
confidence: 99%
See 1 more Smart Citation